2022
DOI: 10.3389/fphar.2022.811808
|View full text |Cite
|
Sign up to set email alerts
|

Icariin: A Potential Molecule for Treatment of Knee Osteoarthritis

Abstract: Background: Knee osteoarthritis (KOA) is a degenerative disease that develops over time. Icariin (ICA) has a positive effect on KOA, although the mechanism is unknown. To investigate drug-disease connections and processes, network pharmacology is commonly used. The molecular mechanisms of ICA for the treatment of KOA were investigated using network pharmacology, molecular docking and literature research approaches in this study.Methods: We gathered KOA-related genes using the DisGeNET database, the OMIM databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 56 publications
0
21
0
1
Order By: Relevance
“…La Icariina también presenta efectos antiosteoporóticos y antiinflamatorios en la OA interfiriendo en la vía de señalización NLRP3/caspasa-1 mediada por liposacáridos (LPS) (68), además inhibe apoptosis de condrocitos, degradación de la matriz ósea y estimula la reparación de los cartílagos (69).…”
Section: Tablaunclassified
“…La Icariina también presenta efectos antiosteoporóticos y antiinflamatorios en la OA interfiriendo en la vía de señalización NLRP3/caspasa-1 mediada por liposacáridos (LPS) (68), además inhibe apoptosis de condrocitos, degradación de la matriz ósea y estimula la reparación de los cartílagos (69).…”
Section: Tablaunclassified
“…ICA has been revealed by many studies to play a crucial role in antioxidation ( Liu XJ. et al, 2021 ; Zheng et al, 2021 ) and anti-inflammatory ( Guangtao et al, 2021 ; Zhang et al, 2022 ). Hua et al found that IL-1β induces significant expression of COX-2 and iNOS and stimulates the production of PGE2 and nitric oxide in human NP cells ( Hua et al, 2018 ).…”
Section: Phytochemicals For the Treatment Of Idd By Targeting Inflamm...mentioning
confidence: 99%
“…4.17 Icariin is the major, effective natural compound isolated from Epimedium and has been shown in several studies to have chondroprotective activity [ 162 ]. Icariin suppressed NFκB signaling pathway in chondrocytes [ 114 , 163 ].…”
Section: Natural Compounds Suppressors Of Cartilage Matrix Degradationmentioning
confidence: 99%